THE THEORETICAL FOUNDATIONS OF SATIRE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Annotation:This article explores the nature and evolution of satire in world literature, tracing its origins from ancient Rome through the Enlightenment to modern times. It highlights satire’s unique role in addressing social and political issues with humor, irony, and critique, distinguishing it from related concepts such as humor, irony, and sarcasm. The essay focuses particularly on Evelyn Waugh’s mastery of satire in his short stories, demonstrating how he skillfully combines satire with parody, grotesque, and allegory to critique society without direct condemnation. Through analysis of literary techniques and examples, the article emphasizes satire’s power as a thoughtful, subtle form of social criticism that engages readers by encouraging reflection rather than overt admonishment.